Restructuring Chinese Higher Education - Zhao, Fang (Education Policy Analysis Archives, 1998)
In this article, the current remarkable trend of institutional amalgamation and the establishment of cross-institutional consortiums in China are examined. The principal purpose of this study is to explore policy options on issues connected with the trend and the significant implications of the trend for the future development of higher education in China. I discuss the outstanding issues raised in the restructuring, the main factors behind them and proposes policy options to redress the adversities of the trend at the end. The article draws on national data as well as a case study. The research reported here is constructive for comparative and empirical research of similar issues in international perspectives.